THE EFFECT OF ELSA SPEAK ON PRONOUNCIATION OF ENGLISH SPEAKING AT VOCATIONAL HIGH SCHOOL - Nuraini, Widya Rizki; Setyawan, Mochamad Ardi; Pambayun, Rizky Nurfida (English Language Teaching Methodology, 2024)
Based on the observations made by the researcher, it appears that certain students continue to experience challenges in pronouncing specific words. The aim of this research is to investigate the impact of the ELSA Speak Application on enhancing students' pronunciation skills. The research design employed was pre-experimental, utilizing a quantitative approach. The researcher implemented cluster sampling, selecting one class comprising 19 students as the sample group. A pronunciation test served as the data collection technique. The researcher conducted a pretest prior to the treatment involving the ELSA Speak Application and subsequently administered a posttest following the treatment. Data collection was executed through this testing method. To analyze the data, the researcher employed the paired sample t-test formula using SPSS 21. The analysis revealed a significant effect of the ELSA Speak Application on improving students' pronunciation.